Endothelial Cells Promote Docetaxel Resistance of Prostate Cancer Cells by Inducing ERG Expression and Activating Akt/mTOR Signaling Pathway - Zhou, Wenhao; Su, Yiming; Zhang, Yu; Han, Bangmin; Liu, Haitao; Wang, Xiaohai (Frontiers in Oncology, 2020)
Docetaxel is a first-line chemotherapy for the treatment of patients with castration-resistant prostate cancer (CRPC). Despite the good initial response of docetaxel, drug resistance will inevitably occur. Mechanisms underlying docetaxel resistance are not well elaborated. Endothelial cells (ECs) have been implicated in the progression and metastasis of prostate cancer. However, little attention has been paid to the role of endothelial cells in the development of docetaxel resistance in prostate cancer. Here, we sought to investigate the function and mechanism of endothelial cells involving in the docetaxel resistance of prostate cancer. We found that endothelial cells significantly promoted the proliferation of prostate cancer cells and decreased their sensitivity to docetaxel. Mechanistically, basic fibroblast growth factor (FGF2) secreted by endothelial cells leads to the upregulation of ETS related gene (ERG) expression and activation of the Akt/mTOR signaling pathway in prostate cancer cells to promote docetaxel resistance. In summary, these findings demonstrate a microenvironment-dependent mechanism mediating chemoresistance of prostate cancer and suggest that targeting FGF/ FGFR signaling might represent a promising therapeutic strategy to overcome docetaxel resistance.